Arbitration in China : a legal and cultural analysis - Fan, Kun (China and international economic law series ;, 2013)
Written for international businessmen, lawyers, academics and students, this book gives the reader a unique insight into real arbitration practice in China, based on a combination of theoretical analysis and practical insights.